Aspects of Art : An Essential Textbook for Students of Art in Pakistan - Marjorie Husain (Karachi Oxford University Press, 2015)
Aspects of Art covers the fundamentals of the theory and practice of art. A guide for teachers as well as students, it aims to motivate students of art to explore great examples of art and their creators, from pre-history to the present time.
Include Dictionary, Illustrations, Bibliography and Index.
An Essential Textbook for Students of Art in Pakistan.
Keywords: Art -- Art - Examinations -- Examinations